Method for long-term room temperature storage of mouse freeze-dried sperm - Yuko Kamada; Kango Yamaji; Natsuki Ushigome; Daiyu Ito; Sayaka Wakayama; Kenichiro Hiraoka; Masaru Hayashi; Kiyotaka Kawai; Teruhiko Wakayama (Scientific Reports)
Abstract Permanent preservation of genetic resources may be indispensable for the future of humanity. This requires liquid nitrogen, as is the case for preserving animal sperm. However, this technique is expensive and poses a risk of irrecoverable sample loss on non-replenishment of liquid nitrogen in case of natural disasters. In this study, we demonstrate that lyophilization may be used as a reliable method for long-term preservation of mouse sperm at room temperature. Sperm from four mouse strains were freeze-dried and stored in a non-temperature controlled room for 5–6 years. Although the ability of the stored sperm to activate oocytes had diminished slightly, healthy offspring were obtained by artificially activating the oocytes after sperm injection. Moreover, the birth rate did not decrease even after ≤ 6 years of storage. Furthermore, owing to its low cost, safety, and ease of storage at any location, we believe that this method could be a major mode of preserving mammalian genetic resources in the future.